Savonius Vertical Axis Wind Turbines: A Review of Design Principles and Fabrication Approaches - Prasad Suryawanshi; Swapnil Jadhav; Wali Ahmed Shaikh; Shubham Sawant; Amol Bhagat (International Journal of Advanced Control and System Engineering, 2024)
The need for renewable energy-based applications is rising in the modern world. The wind turbine is among the most practical energy sources. The best examples of using wind energy to its fullest extent are windmills. One such use for wind energy harvesting is the “Vertical Axis Wind Turbine” project work. In this project, the possibility of producing electricity and supplying it to bus stops, traffic lights, streetlights, etc. was investigated. This turbine would serve as a renewable energy source by producing high-velocity wind when it was erected next to motorways and flyovers. This turbine will use a Savonius blade to lessen air drag. Fibre is used to build blades, so they are lightweight and flexible. It has a DC motor and a spur gear system. This advancement makes producing electricity simple and affordable. As a result, a prototype for a workable arrangement has been created.
Keywords: Design of Blades; Efficiency of VAWT; Electricity Generation; Lift and drag coefficients; Renewable energy; Wind Energy; Wind Turbine